Emerging vistas of Remote Sensing Tools in Pollination Studies - Krishnasamy, Venkateswaran; Sundaraguru, Ramakrishnan; Amala, U. (Sociobiology, 2019)
With the growth of information and technology across the globe, remote sensing applications find a place in the ecological studies of pollinators. The utilization of remote sensing tools in understanding the ecosystem services rendered by the bee pollinators is reviewed here. We discussed how radar and radio telemetry techniques helps to track individual bees, their foraging behaviour and density in relation to altered phenology of flowering crops in a landscape. Role of satellite imagery tools in studying characterizing a landscape affected by anthropogenic factors was discussed.  Monitoring invasive bee species that cause a threat to native bee fauna was explored. We explained the utilization of unmanned aerial vehicles to map the floral resource that influence the density and incidence of pollinators. Remote sensing tools used to measure sequence of pollination events was discussed.